2022
DOI: 10.1371/journal.pone.0261885
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cannabis policy and prevalence of recreational cannabis use among adolescents and young adults in Europe—An interrupted time-series analysis

Abstract: Background Cannabis policy varies greatly across European countries, but evidence of how such policy impacts on recreational cannabis use among young people is conflicting. This study aimed to clarify this association by investigating how changes in cannabis legislation influenced cannabis use. Methods Available data on self-reports of recreational cannabis use among individuals aged 15–34 years was retrieved from EMCDDA. Information on cannabis policy changes was categorized as more lenient (decriminalisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…It may be this common route of administration through inhalation of vaping products that has led young people who use cannabis to opt for vaping rather than smoking it. However, while the overall youth nicotine product use has been variable, trending up from 2017 to 2019 before trending down again between 2019 and 2021[ 40 ], the overall prevalence of cannabis use in young people from multiple countries has remained relatively stable even after medical and/or non-medical cannabis legalization [ 41 , 42 ]. Future research should collect information by delivery method and types of product use to inform preventative efforts.…”
Section: Discussionmentioning
confidence: 99%
“…It may be this common route of administration through inhalation of vaping products that has led young people who use cannabis to opt for vaping rather than smoking it. However, while the overall youth nicotine product use has been variable, trending up from 2017 to 2019 before trending down again between 2019 and 2021[ 40 ], the overall prevalence of cannabis use in young people from multiple countries has remained relatively stable even after medical and/or non-medical cannabis legalization [ 41 , 42 ]. Future research should collect information by delivery method and types of product use to inform preventative efforts.…”
Section: Discussionmentioning
confidence: 99%
“…What is more, in Norway cannabis use is criminalized. Thus, assessing cannabis use within a school-survey may lead to an underreporting of the actual cannabis use prevalence, due to the fear of being identified and so punished for cannabis use [ 45 ]. Although the Ungdata survey is anonymous, this underreporting might be common especially in regions with small adolescent populations.…”
Section: Discussionmentioning
confidence: 99%
“…Although the highest DDDs were observed for European countries of the North (Sweden, Iceland, Norway) and the lowest mainly in those of the West (Netherlands, Austria, Germany), the prevalence of Central/Eastern European countries was visible in those located halfway up the list (Estonia, Czechia, Slovakia), compared to only one country of the South, i.e., Spain. As for cannabinoids, a study by Gabri et al efficiently summarizes cannabis use among adolescents and young adults [ 37 ]. The authors recapitulated the country-specific prevalence of self-reported cannabis use, within which three countries from Southern Europe (Spain, Italy, Portugal) and two from Central/Eastern Europe (Czechia, Slovakia) were included.…”
Section: Discussionmentioning
confidence: 99%